New genera, species and records of Afrotropical Phaneropterinae (Orthoptera, Tettigoniidae) preserved at the Royal Belgian Institute of Natural Sciences, Bruxelles - Massa, Bruno (Zootaxa, 2017)
The results of the study of the rich material of Orthoptera Phaneropterinae at the Royal Belgian Institute of Natural Sciences, Bruxelles, are reported. The following new taxa are described: Dithela longicaudata n. sp. from the Democratic Republic of Congo, Terpnistriella bredoi n. gen. n. sp. from the Democratic Republic of Congo, Mimoscudderia paulyi n. sp. from the Madagascar, Pseudogoetia constanti n. gen. n. sp. from the Democratic Republic of Congo (including a table listing differences with related genera), and Materuana abyssinica n. sp. from the Ethiopia. Some taxonomic and distributional data about the following species are also reported: Melidia claudiae Massa, 2015, Symmetrokarschia africana (Brunner von Wattenwyl, 1878), Eurycorypha ndokiensis Massa, 2016, Eurycorypha prasinata Stål, 1874, Eurycorypha spinulosa Karsch, 1889, two unidentified species of Eurycorypha recorded by Griffini in 1908, Tylopsis irregularis Karsch, 1893, Pardalota asymmetrica Karsch, 1896, Pardalota haasi Griffini, 1908, Pardalota karschiana Enderlein, 1907, Pardalota versicolor Brunner von Wattenwyl, 1878, Poecilogramma cloetensi (Griffini, 1908), Poecilogramma annulifemur Karsch, 1887, Morgenia spathulifera Griffini, 1908, Mimoscudderia picta Carl, 1914 and Angustithorax spiniger Massa, 2015. The following synonymy is established: Plangiopsis shoutedeni Griffini, 1908 = Plangiopsis adeps Karsch, 1896; the latter species, recently moved to the genus Plangiola Bolívar, 1906 is again transferred to the original genus.